2017
DOI: 10.1002/clen.201600333
|View full text |Cite
|
Sign up to set email alerts
|

Application of Partial Least Squares‐Kernel Calibration in Competitive Adsorption Studies Using an Effective Chemically Activated Biochar

Abstract: In this work, chemically activated pine wood was used to prepare biochar, which was used to study the competitive adsorption behavior of four colorants (allura red (AR), brilliant black (BB), tartrazine (TT), and sunset yellow (SY)). Dye concentrations in mixed solutions were simultaneously estimated by using partial least squares Kernel calibration. The analytical recovery of food dyes was 96.7–103.4% and prediction error was 1.4–9.4%. Adsorption isotherms of dyes (at pH 2 and 25°C) from multi‐solute solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
3
0
1
Order By: Relevance
“…As a matter of fact, the modified Langmuir model accounts for the influence of other competing solutes by means of the interaction factor (η). Similar previous results were explained by the fact that one adsorption site cannot be simultane-ously occupied by two solutes, and competitive sorption between pollutants occur when they coexisted in wastewaters [29,51,62]. As for BV3, the P -factor model could match best the equilibrium adsorption data.…”
Section: Equilibrium Modelingsupporting
confidence: 84%
See 2 more Smart Citations
“…As a matter of fact, the modified Langmuir model accounts for the influence of other competing solutes by means of the interaction factor (η). Similar previous results were explained by the fact that one adsorption site cannot be simultane-ously occupied by two solutes, and competitive sorption between pollutants occur when they coexisted in wastewaters [29,51,62]. As for BV3, the P -factor model could match best the equilibrium adsorption data.…”
Section: Equilibrium Modelingsupporting
confidence: 84%
“…A similar trend was reported by Issa et al [29] when they investigated the kinetic biosorption of Allura Red (AR) and Sunset Yellow (SY) by activated pine wood. Authors reported that SY (CF = 0.76) dye manifested stable performance while AR (CF = 0.69) negatively competed with the other dye molecules.…”
Section: Kinetic Study and Modelingsupporting
confidence: 81%
See 1 more Smart Citation
“…Agricultural waste has been used to very less extent for this purpose. The only reported wastes (to the best of our knowledge) as adsorbents either directly or after pyrolysis for removing AR are pinewood, arabica coffee residues, coconut shell, corncob, guargum, peanut hull waste, sawdust, pecan nut shells, luffa cylindrica and bael patra [42–51] …”
Section: Introductionmentioning
confidence: 99%
“…Bu tür numunelerin ayrı ayrı numunelerde analizi için farklı enstrümental tekniklerin kullanıldığı çalışmalarda mevcuttur. βkaroten, spektrofotomerik [8] olarak; sunset yellow, spektrofotometrik olarak [9,10,11], elektrokimyasal olarak [12,13], kolorimetrik olarak [14], yüksek performans sıvı kromatografisi ile [15], floresans yöntemi [16], raman spektroskopisi [17], viskozite [18] ve adsorpsiyon tekniği [19] ile incelenmişlerdir. Literatür incelendiğinde sunset yellow ve β-karotenin birlikte eş zamanlı tayinine rastlanmamıştır.…”
Section: Gi̇ri̇ş (Introduction)unclassified